STUDY OF CHARKOKTA ANGULA PRAMANA OF SHADANGA AND IT’S IMPACT ON PHYSICAL HEALTH (AYUSHDHARA, 2021)
Body parts and their Pramana are specially described in Ayurveda which is an important part of Rachana Sharir. Description of Angula Pramana was found in Vedic Kala, Purana-Upanishad Kala. Samhita Kala like Vrahtai (Charaka Samhita, Sushruta Samhita, Ashtanga Sangraha, Astanga Hridya) Kashyapa Samhita, Bhela Samhita, Sharangadhara Samhita, Vangsena Samhita, and Kautilya Arthashastra. Pramanas are not useful only in Rog and Rogi Pariksha but also useful to know about his/her Ayu such as Hitaayu, Ahitaayu, Sukhayu and Dukhaayu. At the time of Acharya Charaka, the length and breadth of different Anga-Pratyanga was measured by using their own fingers. This technique of measurement is known as Anguli Pramana. Anguli Pramana which is based on Swa-Angula Pramana is used for measuring the dimensions (Ayam, Vistara and Parinaha etc.) of the different Anga Pratyanga of the body. The study was conducted on 200 volunteers in the age group of 16-40 years. One Angula as a unit of Angula Pramana was obtained by measuring the width of Madhyamparva of middle finger of working hand. The measurements were taken in centimetres for standardization as per metric system and then converted into Anguli Pramana based on individual.This article summarizes the facts related to Anguli Pramana from classical literature, Ayurvedic literature and modern literature along with result of our research work to identify the anatomical landmark of Shadanga to measure through Anguli Pramana and its impact on physical health in present era. At present, there are many physical anomalies either they are genetic disorders, endocrine disorders, traumatic injury which results as anatomical disfiguration of body parts that can distinguish from their Anguli pramana or anthropometry.